The Utilization of The Best First Search Algorithm in The Solution of The Traveling Salesman Problem Case In City X - Etza Nofarita Nofarita (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2021)
The heuristic search is part of a method that is often used by people in solving the case of finding the shortest route, the search for the shortest path to solve the distance problem can be converted into a graph structure, where the point represents the city and the side represents the path that connects the two cities. The General and test process is one of the methods in which the case testing uses heuristic functions. The problem that often occurs in this case is to find the shortest path of a city and the various available paths. The process of this method is in the form of determining the distance between cities which can be seen from how far it is traveled so that it can take an alternative to find the shortest path. The main purpose of solving this case is to find alternative ways to find the shortest path and have benefits in saving time and costs so that optimal results are obtained. The use of algorithms in General and test can be used as an information system in making decisions on a travel route. The use of the best first search method in general and tests can be used to search for the shortest path to obtain maximum results